2020
DOI: 10.1128/aem.00342-20
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of the Dynamics of Escherichia coli, Total Coliforms, Enterococcus spp., and Aeromonas spp. in Alternative Irrigation Water Sources: a CONSERVE Study

Abstract: As climate change continues to stress freshwater resources, we have a pressing need to identify alternative (non-traditional) sources of microbially safe water for irrigation of fresh produce. This study is part of the center CONSERVE, which aims to facilitate the adoption of adequate agricultural water sources. A 26-month longitudinal study was conducted at 11 sites to assess the prevalence of bacteria indicating water quality, fecal contamination and crop contamination risk (Escherichia coli, total coliforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…For all water types, higher E. coli counts ( p < 0.05) were observed in the vegetable crop growing (May-October) than non-growing (November-April) season. Additionally, this study found that bacterial counts in reclaimed water generally met microbial standards by federal guidelines or needed minimal mitigation ( Solaiman et al, 2020 ). Another recent work studied the prevalence of Shigatoxigenic E. coli (STEC) and atypical enteropathogenic E. coli (aEPEC) in untreated surface water and reclaimed water in the mid-Atlantic United States ( Haymaker et al, 2019 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For all water types, higher E. coli counts ( p < 0.05) were observed in the vegetable crop growing (May-October) than non-growing (November-April) season. Additionally, this study found that bacterial counts in reclaimed water generally met microbial standards by federal guidelines or needed minimal mitigation ( Solaiman et al, 2020 ). Another recent work studied the prevalence of Shigatoxigenic E. coli (STEC) and atypical enteropathogenic E. coli (aEPEC) in untreated surface water and reclaimed water in the mid-Atlantic United States ( Haymaker et al, 2019 ).…”
Section: Resultsmentioning
confidence: 95%
“…A recent study conducted by Solaiman et al (2020) assessed the prevalence of bacteria indicating water quality, fecal contamination and crop contamination risk ( E. coli , total coliforms, Enterococcus , and Aeromonas ) over a 26-month longitudinal study in the mid-Atlantic region of the United States. For all water types, higher E. coli counts ( p < 0.05) were observed in the vegetable crop growing (May-October) than non-growing (November-April) season.…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli is a thermo-tolerant organism that is part of the coliform group that is considered as an indicator of faecal contamination (Steele and Odumeru, 2004). Studies done previously looking at the water quality in different regions of the United States have utilized E. coli and coliform populations as an indicator for assessing the microbiological safety (McEgan et al 2013;Havelaar et al 2017;Partyka et al 2018;Truitt et al 2018;Solaiman et al 2020). Some have shown a correlation between E. coli or coliform populations with target bacterial pathogens (Salmonella and Shiga-toxigenic E. coli) in surface water (Partyka et al 2016;Truitt et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Non-traditional water sources in the Mid-Atlantic region of the United States were surveyed for Escherichia coli, total coliforms, and enterococci. These organisms were each detected in more than 85% of the 333 samples tested, and E. coli levels were significantly higher during the growing season of May through October, compared to other months [3]. Truitt et al evaluated Virginian surface waters used for agricultural irrigation during 2015 and 2016; Salmonella was detected in 19% of the four hundred samples collected [4].…”
Section: Introductionmentioning
confidence: 99%
“…In many studies where enteric pathogens and fecal contamination of water sources are investigated, the primarily focus on one type of organism [3][4][5][6][7]. However, bacteria and viruses are both found in human feces, but their structural differences create variations in the persistence and efficacy of water treatment technologies.…”
Section: Introductionmentioning
confidence: 99%